Pengaruh Gaya Kepemimpinan Transformasional, Lingkungan Kerja Digital, Dan Kompetensi Karyawan Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Mediasi - Rizki Saputra (Journal Of Informatics And Busisnes, 2026)
This study aims to analyze the effect of transformational leadership style, digital work environment, and employee competence on employee performance, with work motivation as a mediating variable. This research is motivated by the increasing demands of the digital era, which require organizations to adopt adaptive leadership, develop technology-based work environments, and enhance employee competence in order to improve performance sustainably.This study employs a quantitative approach using a survey method. The population of this research consists of employees at the selected company, with a saturated sampling technique applied. Data were collected through questionnaires developed based on indicators of each research variable. The collected data were analyzed using statistical techniques through SPSS, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R²), and mediation testing using the Sobel method.The results indicate that transformational leadership style, digital work environment, and employee competence have a positive and significant effect on employee performance. Furthermore, work motivation also has a positive and significant effect on employee performance. The mediation test results reveal that work motivation significantly mediates the relationship between transformational leadership style, digital work environment, and employee competence on employee performance. The coefficient of determination indicates that a substantial proportion of the variation in employee performance can be explained by the variables examined in this study, while the remaining variation is influenced by other factors outside the research model.This study is expected to provide both theoretical and practical contributions by offering insights for organizations to enhance employee performance through strengthening transformational leadership, improving digital work environments, developing employee competence, and managing work motivation effectively.